2014
DOI: 10.4141/cjps2013-234
|View full text |Cite
|
Sign up to set email alerts
|

Condensed tannins concentration of selected prairie legume forages as affected by phenological stages during two consecutive growth seasons in western Canada

Abstract: SummaryApproximately 4.9 to 5.0 M ha of cultivated marginal land in Western Canada is environmentally unsustainable and would benefit from conversion to permanent cover from current annual cropping. Since 2001, re-establishment of native grasslands into marginal cropland has been successfully accomplished using conventional seeding technology and a productive and sustainable pasture grazing system has been achieved. The current native grasslands are providing high quality forage for yearling grazing livestock,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 57 publications
7
40
0
6
Order By: Relevance
“…Furthermore, the CT in the PPC was about 47 g/kg DM, but only trace amounts of CT were detected in the orts. The CT concentration in stems of PPC is lower than that of the leaves ranging from 10 to 16.8 g/kg DM (Jin et al, 2012;Li et al, 2014). If portions of PPC and Alf were consumed to a similar extent, there would be detectable amount of CT in the orts.…”
Section: Forage Composition and Feed Intakementioning
confidence: 94%
See 4 more Smart Citations
“…Furthermore, the CT in the PPC was about 47 g/kg DM, but only trace amounts of CT were detected in the orts. The CT concentration in stems of PPC is lower than that of the leaves ranging from 10 to 16.8 g/kg DM (Jin et al, 2012;Li et al, 2014). If portions of PPC and Alf were consumed to a similar extent, there would be detectable amount of CT in the orts.…”
Section: Forage Composition and Feed Intakementioning
confidence: 94%
“…In addition, only traces CT were detected from orts that consisted of stem only (data not shown). It has been shown that majority of CT in PPC is in flower and leaves (Jin et al, 2012;Li et al, 2014) which were ingested by the animals. Accordingly, CT concentrations estimated in ingested diet (35-36 g/kg DM) was numerically higher than that estimated for diet offered (29 g/kg DM).…”
Section: Forage Composition and Feed Intakementioning
confidence: 99%
See 3 more Smart Citations